2017
DOI: 10.1177/1078345816684833
|View full text |Cite
|
Sign up to set email alerts
|

Caring to Learn and Learning to Care

Abstract: The increasing numbers of aging and chronically ill prisoners incarcerated in Western nations is well documented, as is the growing need for prison-based palliative and end-of-life care. Less often discussed is specifically how end-of-life care can and should be provided, by whom, and with what resources. One strategy incorporates prisoner volunteers into end-of-life services within a peer care program. This article reports on one such program based on focused ethnographic study including in-depth interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…The review identified 23 articles, 16 reporting qualitative methods2 3 29–42(table 3), six reporting quantitative methods8 9 43–46(table 4) and one reporting mixed methods4(table 3). Methodological diversity was high across all groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The review identified 23 articles, 16 reporting qualitative methods2 3 29–42(table 3), six reporting quantitative methods8 9 43–46(table 4) and one reporting mixed methods4(table 3). Methodological diversity was high across all groups.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles reported findings from six studies based in the USA,8 9 29–33 36 39–43 four articles reported findings from three studies based in the UK,4 35 38 45 three articles reported findings from two studies based in Switzerland,3 34 37 two articles reported findings from one study in France2 46 and one article reported findings from a study in India 44. The articles reported on a broad range of areas, including prison healthcare facilities,43 45 the health of dying prisoners and causes of death,8 9 44 46 elderly and dying prisoners views on issues related to palliative and end of life care in prisons3 4 34 36 40 and inmate volunteer caregivers 30–33 42. Of the 19 studies which sampled prisoners (or their case records),2–4 8 9 29–34 36–38 40–42 44 46 12 dealt exclusively with male prisoners,4 8 29 30 32 33 36–38 40–42 and seven with male and female prisoners 2 3 9 31 34 44 46…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations